Using protection motivation theory to support patient adherence in healthcare settings: A scoping review - Olivia Hawksworth; Jemima Solt; Dowon Jang; Paul Norman; Daniel Hind; Raveen Jayasuriya (PLoS ONE, 2025)
Background Protection motivation theory (PMT) shows promise as a basis for motivating healthy behaviours in healthcare settings. There has been no systematic overview of how PMT has been translated into clinical practice and which translation strategies effectively improve outcomes. Objectives This scoping review aimed to systematically map and synthesise existing literature on PMT-based interventions targeting health behaviours in healthcare contexts. Methods Medline, PsycINFO, and EMBASE were searched for studies applying PMT within healthcare contexts. Eligible populations had a clinical condition. To be eligible, studies had to report a healthcare-delivered PMT intervention with adherence outcomes directly benefiting participants. Two reviewers extracted data on study features, intervention characteristics including behaviour change techniques employed, PMT constructs addressed, results, and research recommendations. Findings were summarised narratively and tabulated. Results Thirteen studies published between 1998 and 2023 met the eligibility criteria, including 12 randomised trials. Studies addressed acute and chronic conditions across primary, secondary, and non-clinical settings. Half significantly improved behaviour outcomes in intervention groups. All targeted coping-self-efficacy and perceived threat-severity PMT constructs to some degree. Combinations of behaviour change techniques did not clearly differentiate successful outcomes. Studies recommended longer follow-up, clarifying effective PMT component combinations, and drawing on multiple behaviour theories. Discussion Despite heterogeneity in how PMT interventions were operationalised, they show potential benefits for motivating adherence to healthy behaviours. To enable optimisation and dissemination, consistent nonadherence detection and reporting methods are critical. Further research should include translation of PMT to other healthcare settings, refining methodology and implementing well-powered effectiveness trials in routine care.